Some remarks on the property (N) of Luzin - Kharazishvili, Alexander B. (Annales Mathematicae Silesianae, 1995)
We consider the classical property (N) of Luzin for various mappings in connection with a measure extension problem. We give some examples of Borel measurable mappings and of Lebesgue measurable mappings which transform all compact sets with measure zero into sets with measure zero but do not have the property (N) of Luzin.